Crop Load, Fruit Thinning and their Effects on Fruit Quality of Apple (Malus domestica Borkh.) - Racskó, József (Acta Agraria Debreceniensis, 2006)
Crop load, a quantitative parameter used by industry, is generally defined as the number of fruit per tree. It is often expressed in terms of number of fruit per trunk cross-sectional area (fruit/TCSA). Crop load is the most important of all factors that influence fruit size, and the removing of a part of the crop is the most effective way to improve fruit size. The potential size of a given pome fruit is determined early in the season and growth proceeds at a relatively uniform rate thereafter. This uniform growth rate permits the accurate prediction of the harvest size of the fruit as early as mid-summer. The growth rate, once established, is not easily altered, and fruit numbers, therefore, can affect fruit size only within definite limits and maximum effectiveness requires adjustment in fruit numbers relatively early in the season. It was established, that „thinning does not change a potentially small fruit into a large fruit, but rather insures that a potentially large fruit will size properly.” Emphasis should be on estimating fruit numbers rather than fruit size. Fruit thinning can quickly reach the point of diminishing returns. Rather than a high percentage of large fruits, the objectives of thinning should be the elimination of the smallest fruits, improved fruit quality and annual production. Fruit thinning is accomplished by hand or chemical thinning. Chemical thinners are separated into categories as bloom thinners and post-bloom thinners. Early removal of potential fruit (blossom thinning) is currently used in many apple producing areas to enhance flower initiation for next year’s crop and thus, return bloom. It also results in reduced competition for photosynthates. Blossom thinners usually have a caustic effect on floral parts. The amount of fruit left on a tree should be determined by the vigor and general condition of the tree. Leaf area per fruit affects the number of spurs flowering the following season. It can be difficult to separate timing and fruit number effects in crop loading studies, as abscission rates after hand thinning of retained flowers/fruitlets tend to very with the time of hand thinning.